Sentinel node biopsy using blue dye and technetium99 in advanced gastric cancer: anatomical drainage and clinical application - F.A.V. Santos; A.P. Drummond-Lage; M.A. Rodrigues; M.A. Cabral; M.S. Pedrosa; H. Braga; A.J.A. Wainstein (Brazilian Journal of Medical and Biological Research, 2016)
Lymph node metastases are an independent prognosis factor in gastric carcinoma (GC) patients. Radical lymphadenectomy can improve survival but it can also increase surgical morbidity. As a principle, sentinel node (SN) navigation surgery can avoid unnecessary lymphadenectomy without compromising prognosis. In this pilot study, 24 patients with untreated GC were initially screened for SN navigation surgery, of which 12 were eligible. Five patients had T2 tumors, 5 had T3 tumors and 2 had T1 tumors. In 33% of cases, tumor diameter was greater than 5.0 cm. Three hundred and eighty-seven lymph nodes were excised with a median of 32.3 per patient. The SN navigation surgery was feasible in all patients, with a median of 4.5 SNs per patient. The detection success rate was 100%. All the SNs were located in N1 and N2 nodal level. In 70.9% of cases, the SNs were located at lymphatic chains 6 and 7. The SN sensitivity for nodal staging was 91.6%, with 8.3% of false negative. In 4 patients who were initially staged as N0, the SNs were submitted to multisection analyses and immunohistochemistry, confirming the N0 stage, without micrometastases. In one case initially staged as negative for nodal metastases based on SN analyses, metastases in lymph nodes other than SN were found, resulting in a 20% skip metastases incidence. This surgery is a reproducible procedure with 100% detection rate of SN. Tumor size, GC location and obesity were factors that imposed some limitations regarding SN identification. Results from nodal multisection histology and immunohistochemistry analysis did not change initial nodal staging.